2006
DOI: 10.1177/0022022106292081
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation and Contrast Effects in Cultural Frame Switching

Abstract: This study examines how the valence of cultural cues in the environment moderates the way biculturals shift between multiple cultural identities. The authors found that when exposed to positive cultural cues, biculturals who perceive their cultural identities as compatible (high bicultural identity integration, or high BII) respond in culturally congruent ways, whereas biculturals who perceive their cultural identities as conflicting (low BII) respond in culturally incongruent ways. The opposite was true for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…Participants in this study were overall more acculturated with Chinese culture ( M = 3.78, SD = 0.43) than American culture ( M = 3.25, SD = 0.42), t (136) = −10.31, p < 0.05, Cohen's d = −0.88, in line with past studies on biculturals that have also shown similar acculturation patterns (Tsai et al, 2000; Benet-Martínez et al, 2002; Benet-Martínez and Haritatos, 2005; Cheng et al, 2006; Miramontez et al, 2008; Zou et al, 2008). Therefore, despite the differences found in the levels of acculturation in American and Chinese cultures, the sample was bicultural due to being acculturated with both cultures to some extent.…”
Section: Resultssupporting
confidence: 82%
“…Participants in this study were overall more acculturated with Chinese culture ( M = 3.78, SD = 0.43) than American culture ( M = 3.25, SD = 0.42), t (136) = −10.31, p < 0.05, Cohen's d = −0.88, in line with past studies on biculturals that have also shown similar acculturation patterns (Tsai et al, 2000; Benet-Martínez et al, 2002; Benet-Martínez and Haritatos, 2005; Cheng et al, 2006; Miramontez et al, 2008; Zou et al, 2008). Therefore, despite the differences found in the levels of acculturation in American and Chinese cultures, the sample was bicultural due to being acculturated with both cultures to some extent.…”
Section: Resultssupporting
confidence: 82%
“…In this paper, we have focused on effects that might be termed assimilative. However, one might hypothesize: To the extent that an action raises the salience of an ideal that the person believes they either cannot meet or do not want to meet, the effect may be to produce contrastive behavior (Cheng, Lee, & Benet-Martinez, 2006;Dijksterhuis et al, 1998;Herr, Sherman, & Fazio, 1983;Likowski et al, 2008;Mussweiler, 2006;Schubert & Hafner, 2003). (3) In the present paper, we have focused on what might be called hard embodiment-that is, the way ideals, values, action tendencies, and so on are embodied in the way we actually move and comport our physical bodies.…”
Section: Complexities Of Embodimentmentioning
confidence: 99%
“…Such effects are interesting from the perspective of acculturation theory, which emphasizes a bidimensional approach, in which orientation toward both cultures is taken into account (Sam & Berry, 2010). Moreover, if orientation toward one culture increases, and simultaneously orientation toward the other decreases, this possibly suggests the experience of incompatibility between both cultures (Cheng, Lee, & Benet-Martinez, 2006; Ward, 2013). In the present study, such an effect was confined to the Antillean Dutch group, which is interesting because it suggests specific acculturation patterns of this group (on whom detailed insights in acculturation patterns are scarce).…”
Section: Discussionmentioning
confidence: 99%